Comparative Status of Sequestered Carbon Stock of Azadirachta indica and Conocarpus erectus at the University of Karachi Campus, Pakistan - Ajani, Amber; Shams, Zafar Iqbal (International Journal of Environment, 2016)
Carbon sequestration by trees is one of the most cost-effective and efficient methods to remove carbon dioxide from atmosphere since trees remove and store carbon at higher rates compared to other land covers. Carbon storage by trees typically ranges from 1 to 8 MgC ha-1 yr-1.The carbon is sequestered in different parts of the trees as biomass. The measurements of biomass provide reasonably accurate estimate of the amount of carbon that was removed from lower troposphere over the years. Therefore, the present study investigates and compares the carbon stock of native Azadirachta indica and exotic Conocarpus erectus, which are extensively cultivated in the campus of the University of Karachi, Pakistan. The above-ground and below-ground biomass of 327 trees of A. indica and 253 trees of C. erectus were estimated by using non-destructive method. The average carbon content of A. indica is calculated to be 662.32 + 1144.81 Kg while that of C. erectus is 192.70 + 322.60 Kg. The independent t-test analysis showed significant difference (p < 0.001) between the means of the carbon content of both the species. The carbon contents of two different species were also correlated with bole’s diameter at breast height (DBH) and tree’s height. The analysis demonstrated greater correlation between the carbon content and the DBH of both the species compared to that with their height. The study will help to understand the carbon sequestration potential of two different types of species for planting particularly in urban area of the world. INTERNATIONAL JOURNAL OF ENVIRONMENT Volume-5, Issue-2, March-May 2016, Page: 89-97